Advance planning for research participation: Time to translate this innovation into practice. (13th December 2022) - Ries, Nola; Johnston, Briony; Jeon, Yun‐Hee; Mansfield, Elise; Nay, Rhonda; Parker, Deborah; Schnitker, Linda; Sinclair, Craig
Abstract: Objectives: Advance planning for research is a process that involves thinking about, discussing and expressing preferences for taking part in research during future periods of incapacity. The process may include making an advance research directive and naming trusted people to be involved in decisions about research participation. Advance research planning could help to overcome barriers to including people with dementia in research. To encourage innovation in this area, this article presents recommendations informed by a stakeholder workshop that brought together consumer representatives and representatives active in dementia, ageing and health‐related research, policy‐making, advocacy and service delivery in health and aged care. Methods: An online workshop where 15 stakeholders shared perspectives and suggestions for implementing advance research planning, with a focus on research involving people with dementia. Results: Raising awareness of advance research planning requires multi‐faceted strategies. Training and resources are needed for researchers, ethics committees and organisations regarding this form of advance planning and the use of research directives. Like any form of advance planning, planning ahead for research must be a voluntary, informed and person‐centred process. There is a lack of uniform legal rules on research involving people who lack the capacity to consent; however, advance research directives could, in principle, inform decisions about research participation. Conclusions: As a matter of law, policy and practice, people are encouraged to plan ahead in many areas of their life. Research planning has been relatively neglected, and the recommendations offered here aim to encourage innovation in research and implementation in this area.